The bronze screen : Chicana and Chicano film culture - Fregoso, Rosa Linda (University of Minnesota Press, 1993)
Explores Chicana and Chicano popular culture through contemporary representations in both Hollywood commercial and independent cinema.
Keywords: Culture in motion pictures.; Mexican Americans in motion pictures.; Culture au cinéma.; Américains d'origine mexicaine au cinéma.; PERFORMING ARTS -- Film & Video -- General.; PERFORMING ARTS -- Reference.; POLITICAL SCIENCE -- Essays.; POLITICAL SCIENCE -- Government -- General.; POLITICAL SCIENCE -- Government -- National.; POLITICAL SCIENCE -- Reference.; Culture in motion pictures; Mexican Americans in motion pictures